Flexible self-healing electrode with micro-convex peak-nanowire array structure as well as preparation method and application of flexible self-healing electrode
By using a flexible self-healing electrode fabrication method with a micro-convex peak-nanowire array structure, the problems of operational complexity and poor adhesion of existing self-healing materials in the field of flexible electronics are solved, achieving efficient self-healing and conductivity restoration of liquid metal, and improving the reliability and stability of the device.
Patent Information
- Application Number
- CN202511494733.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2026-01-16
AI Technical Summary
Existing self-healing materials in the field of flexible electronics suffer from problems such as complex operation, decreased conductivity, loss of mechanical strength, strong environmental dependence, and poor adhesion, making it difficult to achieve stable integration and long-term use of liquid metal devices.
A method for fabricating a flexible self-healing electrode using a micro-peak-nanowire array structure includes acid etching, heat treatment, oxygen plasma treatment, and polymer solution treatment to form a metal nanowire array, and a liquid metal layer is formed on its surface. Combined with encapsulation lamination technology, a self-healing electrode with capillary action and liquid storage space is constructed.
It achieves efficient self-healing without external intervention, improves the reliability and conductivity of the device in long-term, dynamic working environments, enhances the bonding force between the flexible substrate and the metal layer, and solves the problem of easy detachment of liquid metal.
Smart Images

Figure CN121341935A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of flexible electronics, in particular to a flexible self-healing electrode with a micro-bump-nanowire array structure and a preparation method and application thereof. BACKGROUND
[0002] Currently, self-healing materials show great potential in the field of flexible electronics, especially in smart responsive electrodes and soft pressure sensors. However, the existing self-healing materials in the prior art still have many defects. For example, many self-healing materials have complex operation during the healing process, require external stimulation or manual intervention, and often have significant conductivity degradation and severe mechanical strength loss after healing. In addition, the healing speed of existing self-healing materials is slow, and they have strong dependence on environmental conditions (such as temperature and humidity), which limits their application in complex or extreme environments.
[0003] As a new type of self-healing material, liquid metal has attracted attention in the field of flexible electronics and robotics due to its unique room-temperature fluidity, good electrical conductivity, and environmental adaptability. However, liquid metal-based self-healing devices still face a series of technical bottlenecks: first, the mechanical strength of liquid metal itself is low and prone to deformation or rupture; second, the surface of liquid metal is prone to oxidation, which affects its fluidity and conductivity; third, the adhesion between liquid metal and flexible substrate is poor, and it is easy to peel off or fall off during repeated deformation; in addition, the existing packaging process is complex, making it difficult to achieve stable integration and long-term use of liquid metal devices. SUMMARY
[0004] The purpose of the present application is to overcome the shortcomings of the prior art, and to provide a flexible self-healing electrode with a micro-bump-nanowire array structure and a preparation method and application thereof. By utilizing the excellent room-temperature fluidity and high electrical conductivity of liquid metal, and combining the capillary action and liquid storage space provided by the micro-bump-nanowire array structure, when the electrode cracks due to fatigue, the liquid metal can quickly flow to and fill the damaged area, automatically restoring the conductive path, achieving efficient self-healing without external intervention, and significantly improving the reliability of the device in long-term and dynamic working environments.
[0005] To achieve the above purpose, the present application provides a preparation method of a flexible self-healing electrode with a micro-bump-nanowire array structure, comprising the following steps: S1. providing a flexible substrate with a microstructure; S2. sequentially performing acid etching treatment and heat treatment on the flexible substrate in S1 to form a micro-bump structure on the surface of the flexible substrate; S3. sequentially performing oxygen plasma treatment and polymer solution treatment on the flexible substrate treated in S2; S4. Forming a metal nanowire array on the surface of the flexible substrate treated in S3; S5. Forming a liquid metal layer on the surface of the metal nanowire array to obtain a core layer; S6. Laminating and bonding the encapsulation in the order of the first encapsulation layer, the core layer, and the second encapsulation layer to obtain a flexible self-healing electrode with a micro-bump-nanowire array structure.
[0006] Preferably, in S1, the flexible substrate with microstructure is provided by mixing a polydimethylsiloxane prepolymer and a curing agent, coating on a template, peeling off after curing to obtain a flexible substrate with microstructure.
[0007] Preferably, the mass ratio of the polydimethylsiloxane prepolymer and the curing agent is (8-12):1; the template includes sandpaper; the curing temperature is 75-85℃, and the curing time is 1.5-2.5h.
[0008] Preferably, in S2, the acid etching treatment includes: immersing the flexible substrate in a nitric acid solution; the immersion temperature is 25-40℃, and the immersion time is 10-30min. In S2, the heat treatment is carried out in an inert atmosphere; the heating rate of the heat treatment is 2-5℃ / min, the target temperature is 145-155℃, and the holding time is 1-2h.
[0009] Preferably, in S3, the discharge power of the oxygen plasma treatment is 100-200W, and the oxygen flow rate is 20-40sccm. In S3, the polymer solution treatment includes: immersing the flexible substrate treated by the oxygen plasma treatment in a polyvinyl alcohol solution with a mass fraction of 1-5% for 5-15min.
[0010] Preferably, in S4, forming a metal nanowire array on the surface of the flexible substrate treated in S3 includes: (1) depositing a metal seed layer on the surface of the flexible substrate by magnetron sputtering; (2) immersing the flexible substrate with the deposited metal seed layer in an activation solution containing metal ions for activation treatment; (3) immersing the flexible substrate after the activation treatment in an aqueous solution containing a metal salt and a reducing agent for reaction to grow a metal nanowire array on the surface of the flexible substrate.
[0011] Preferably, in S5, forming a liquid metal layer on the surface of the metal nanowire array includes: electrodepositing an indium layer on the surface of the metal nanowire array, and introducing gallium to contact the indium layer and undergo alloying reaction.
[0012] Preferably, in S6, the first encapsulation layer and the second encapsulation layer respectively include a polyimide film, a polyethylene terephthalate film, or a polydimethylsiloxane film.
[0013] The application further provides a flexible self-healing electrode with a micro-peak-nanowire array structure, which is prepared according to the preparation method of the flexible self-healing electrode with the micro-peak-nanowire array structure.
[0014] The application further provides application of the flexible self-healing electrode with the micro-peak-nanowire array structure in a flexible electronic device.
[0015] The application has the following beneficial effects: 1. The application provides a preparation method of a flexible self-healing electrode with a micro-peak-nanowire array structure, which comprises the following steps: providing a flexible substrate with a microstructure; sequentially performing acid etching treatment, heat treatment, oxygen plasma treatment and polymer solution treatment; forming a metal nanowire array on the surface of the flexible substrate subjected to the above treatments; forming a liquid metal layer on the surface of the metal nanowire array to obtain a core layer; and performing lamination and bonding encapsulation in the order of a first encapsulation layer, the core layer and a second encapsulation layer to obtain the flexible self-healing electrode with the micro-peak-nanowire array structure. The application utilizes the excellent room-temperature fluidity and high conductivity of liquid metal, and the capillary action and liquid storage space provided by the micro-peak-nanowire array structure. When the electrode is cracked due to fatigue, the liquid metal can quickly flow to and fill the damaged area, automatically restore the conductive path, and realize efficient self-healing without external intervention, thereby significantly improving the reliability of the device in a long-term and dynamic working environment. Further, the application constructs a regular micro-peak structure on the surface of the flexible substrate through acid etching treatment and heat treatment. The structure effectively enhances the bonding force between the flexible substrate and the metal layer through mechanical interlocking, increased contact area and relieved interface stress. In combination with the synergistic surface modification of oxygen plasma and polymer solution, the roughness and wettability of the substrate surface are further improved, thereby fundamentally solving the technical problems of easy falling off of the metal conductive layer on the flexible substrate and poor interface stability. The composite structure of the micro-peak-nanowire array in the application synergistically acts on the macro and micro levels: the micro-peak structure effectively disperses external stress and reduces stress concentration; and the nanowire array with high specific surface area provides an excellent three-dimensional conductive network and a powerful capillary driving path. This design enables the electrode to simultaneously have high conductivity, excellent mechanical flexibility and efficient self-healing capability. The entire process flow of the application has mild conditions, avoids damage to the flexible substrate and functional materials caused by high temperature, and has good compatibility with mainstream flexible electronic device preparation technologies. The prepared electrode has the characteristics of flexibility, conductivity, stretchability and self-healing, and is suitable for frontier fields such as flexible display, wearable devices, soft robots and human-computer interaction, which have extremely high reliability requirements, and provides a key material basis for the next generation of high-performance flexible electronic devices.
[0016] 2. The electrodeposition of an indium layer on the nanowires provides both a key interface for liquid metal alloying and effective protection against oxidation of the copper nanowires, ensuring long-term stability of the electrode performance. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 is a schematic diagram of the preparation process of the core layer in the present application; Figure 2 is a schematic diagram of the structure in the preparation process of the core layer in the present application; Figure 3 is a schematic diagram of the contact angle of different flexible substrates in Example 1-Example 3 of the present application; Figure 3 a) in is a schematic diagram of the contact angle of PDMS in Example 1, Figure 3 b) in is a schematic diagram of the contact angle of PDMS-A in Example 3, Figure 3 c) in is a schematic diagram of the contact angle of PDMS-A in Example 2, Figure 3 d) in is a schematic diagram of the contact angle of PDMS-A in Example 1; Figure 4 is a schematic diagram of the contact angle of PDMS-A in Example 1, Example 2 and Example 4-11 of the present application; Figure 5 is a schematic diagram of the contact angle of PDMS-A in Example 1, Example 4-7, Example 12-26, Comparative Example 1-5 of the present application; Figure 6 is a real physical characterization diagram of PDMS, Cu / PDMS and Ga / Cu / PDMS in Example 1 of the present application; Figure 6 a) in is a real physical characterization diagram of PDMS in Example 1, Figure 6 b) in is a real physical characterization diagram of Cu / PDMS in Example 1, Figure 6 c) in is a real physical characterization diagram of Ga / Cu / PDMS in Example 1; Figure 7 is a schematic diagram of the process of obtaining In / Cu / PDMS from Cu / PDMS in Example 1 of the present application; Figure 8 is a morphology characterization comparison diagram of the scratch after manufacturing by different materials in Example 1 of the present application; Figure 8 a) in is a morphology characterization diagram of the scratch after manufacturing by Cu / PDMS, Figure 8 b) in is a morphology characterization diagram of the scratch after manufacturing by Ga / Cu / PDMS. DETAILED DESCRIPTION
[0018] The present application provides a preparation method of a flexible self-healing electrode with a micro-bump-nanowire array structure, comprising the following steps: S1. providing a flexible substrate with a microstructure; S2. sequentially performing acid etching treatment and heat treatment on the flexible substrate in S1 to form a micro-convex structure on the surface of the flexible substrate; S3. sequentially performing oxygen plasma treatment and polymer solution treatment on the flexible substrate treated in S2; S4. forming a metal nanowire array on the surface of the flexible substrate treated in S3; S5. forming a liquid metal layer on the surface of the metal nanowire array to obtain a core layer; S6. laminating and bonding the encapsulation layers in the order of the first encapsulation layer, the core layer and the second encapsulation layer to obtain a flexible self-healing electrode with a micro-convex-nanowire array structure.
[0019] In the present application, in S1, the flexible substrate with microstructure is prepared by mixing polydimethylsiloxane prepolymer and curing agent, stirring for 5-10 min to obtain slurry; vacuumizing (removing air bubbles in the slurry) to a vacuum degree of ≤0.1 MPa, coating the defoaming treated slurry on a template, and placing it on a flat spin coater stage, and performing spin coating at a speed of 150-250 rpm to make the slurry uniform in thickness at each part of the template, then standing at room temperature for 25-35 min, and finally peeling off after curing to obtain a flexible substrate with microstructure (a flexible substrate with rough surface).
[0020] In the present application, the polydimethylsiloxane prepolymer includes one or more of dimethyl methyl hydrogen (siloxane and polysiloxane) (CAS No.: 68037-59-2), vinyl-terminated polydimethylsiloxane (CAS No.: 68083-19-2), and dimethylvinylated and trimethylated silicon dioxide (CAS No.: 68988-89-6).
[0021] In the present application, the curing agent includes methylvinylcyclosiloxane (CAS No.: 2554-06-5).
[0022] In the present application, the thickness of the flexible substrate with microstructure is 550-650 μm.
[0023] In the present application, the mass ratio of polydimethylsiloxane prepolymer to curing agent is (8-12):1; the template includes sandpaper, the mesh number a of the sandpaper is in the range of 0
[0024] In the present application, the flexible substrate with microstructure is soaked in ethanol and ultrasonically treated at 160-200 W for 10-20 min to remove oil stains on the surface, and then subjected to acid etching treatment in S2.
[0025] In the present application, in S2, the acid etching treatment comprises: immersing the flexible substrate in a nitric acid solution with a mass fraction of 60-70%; the immersion temperature is 25-40℃, and the immersion time is 10-30 min.
[0026] The surface modification can be effectively achieved within the range of the immersion time; if the time is too short, the surface modification degree is insufficient; and if the time is too long, excessive corrosion can occur, resulting in a decrease in the mechanical properties of the substrate.
[0027] In the present application, after the acid etching treatment, water washing and drying are sequentially performed.
[0028] In the present application, in S2, the heat treatment is performed in an inert atmosphere; the inert atmosphere comprises nitrogen; the heating rate of the heat treatment is 2-5℃ / min, the target temperature is 145-155℃, and the holding time is 1-2 h.
[0029] In the present application, the heat treatment causes the acid etching layer obtained by the acid etching treatment to further oxidize and crosslink and to shrink, and a strain difference is generated between the acid etching layer and the untreated substrate inside due to the difference in thermal expansion behavior, thereby inducing the formation of a random surface micro-convex peak structure.
[0030] In the present application, in S3, the discharge power of the oxygen plasma treatment is 100-200 W, the oxygen flow rate is 20-40 sccm, and the time is 145-155 s.
[0031] In the present application, in S3, the polymer solution treatment comprises: immersing the flexible substrate subjected to the oxygen plasma treatment in a polyvinyl alcohol (PVA) solution with a mass fraction of 1-5% for 5-15 min, so that the PVA molecules are fully adsorbed and form a uniform coating on the surface of the substrate. If the immersion time is too short, the coating can not be completely covered, and if the time is too long, the PVA molecules can be excessively accumulated, affecting the uniformity of subsequent drying.
[0032] In the present application, after the immersion, the sample is taken out, clamped by tweezers, and gently removed of residual droplets on the surface, so as to avoid the formation of uneven spots during the drying process; then the sample is placed on a hot plate with a uniform temperature of 85-95℃ for drying, so as to rapidly evaporate the water and solidify and crosslink the PVA molecules on the surface of the substrate, and finally form a stable hydrophilic modified layer.
[0033] In the present application, the preparation method of the polyvinyl alcohol solution comprises: mixing polyvinyl alcohol and water, and standing for 5-15 min to fully swell the polyvinyl alcohol; after the standing, first heating and stirring at 85-95℃ for 55-65 min to completely dissolve the polyvinyl alcohol; then heating and stirring at 60-70℃ for 175-185 min to fully stretch the molecular chains and homogenize the solution; and finally cooling to room temperature, and adding water to the original mass of the system to compensate for the evaporation loss, to obtain a polyvinyl alcohol solution with a target mass fraction.
[0034] By combining the oxygen plasma treatment with the polymer solution treatment, the surface properties of the flexible substrate can be synergistically optimized. First, the high-pressure ionized oxygen plasma is generated to bombard the flexible substrate with a surface micro-convex structure, so as to further increase the surface roughness of the flexible substrate and reduce the surface energy, thereby improving the wettability of the surface of the flexible substrate; then the polymer solution treatment is performed to further strengthen the effect, so as to significantly enhance the adhesion between the flexible substrate and the subsequent metal conductive layer.
[0035] In the present application, in S4, the formation of the metal nanowire array on the surface of the flexible substrate treated in S3 comprises: (1) depositing a metal seed layer on the surface of the flexible substrate by using a magnetron sputtering method; (2) soaking the flexible substrate on which the metal seed layer is deposited in an activation solution containing metal ions to perform activation treatment; (3) soaking the flexible substrate after the activation treatment in an aqueous solution containing a metal salt and a reducing agent to perform reaction, so as to grow the metal nanowire array on the surface of the flexible substrate.
[0036] In the present application, in step (1), the flexible substrate treated in S3 is placed in a sputtering chamber, and argon gas is introduced into the chamber as a working gas. Under a sputtering power of 140-160 W and a sputtering temperature of 110-130°C, the deposition rate is controlled at 15-25 nm / min by adjusting the gas pressure. Under the action of a high-voltage electric field, the argon gas is ionized to form a plasma, and the ions in the plasma bombard the target material, so that the target material atoms are sputtered and deposited on the surface of the substrate. Under this condition, the titanium layer is sputtered for 290-310 s first to enhance the interfacial adhesion, and then the copper layer is continuously sputtered for 85-95 min, so as to form a copper seed layer.
[0037] In the present application, in step (2), the preparation method of the activation solution containing metal ions comprises the following steps: PdCl2 is slowly added into a hydrochloric acid solution with a concentration of 0.08-0.12 mol / L, and the mixture is stirred at 45-55°C until PdCl2 is completely dissolved, and then water is added to obtain the activation solution containing metal ions.
[0038] In the present application, the mass-volume ratio of PdCl2 and the hydrochloric acid solution is 3-7 mg: 15-25 mL, and the mass-volume ratio of PdCl2 and the activation solution containing metal ions is 3-7 mg: 45-55 mL.
[0039] In the present application, in step (2), the activation treatment is performed at a temperature of 35-45°C for 3-7 min, so that the metal ions (Pd ions) are fully and uniformly adsorbed and penetrated into the active sites of the surface layer of the substrate.
[0040] In the present application, after the activation treatment is completed, the sample is taken out and washed with water to remove the unabsorbed free metal ions and byproducts, preventing them from causing non-uniform deposition in the subsequent steps, and then dried under a nitrogen atmosphere for 1-2 min to keep the surface clean and activated and avoid the interference of impurities or oxygen in the air on the reaction activity.
[0041] In the present application, step (3) comprises the following steps: in a fume hood, dissolve sodium citrate in water, then add copper sulfate pentahydrate, stir until completely dissolved, then use a 0.3 mol / L sodium hydroxide solution to adjust the pH of the system to 8.5-9.5 to obtain a mixed solution; horizontally fix the sample upwards and immerse it in the mixed solution at a temperature of 55-65℃, keeping the sample edge at a distance of not less than 10 mm from the liquid surface (the vertical distance between the uppermost edge of the sample and the horizontal surface of the solution) to avoid non-uniform edge deposition caused by gas-liquid interface disturbance and capillary effect. After placing the sample, slowly add a 0.3 mol / L ascorbic acid solution, maintain gentle stirring throughout the reaction process, and after 28-32 min of reaction, take out the sample and quickly immerse it in water and shake it gently for 0.5-1.5 min, and then dry it under a nitrogen stream.
[0042] In the present application, the mass-volume ratio of water, sodium citrate, copper sulfate pentahydrate, and ascorbic acid solution is 90-110 mL: 28-32 g: 23-27 g: 145-155 mL.
[0043] In the process of S4, the metal ions undergo nucleation, reduction, and crystal preferential orientation growth on the substrate surface, finally forming a uniform, dense, and regularly oriented metal nanowire array.
[0044] In the present application, in S5, the formation of the liquid metal layer on the surface of the metal nanowire array comprises: electrodepositing an indium layer on the surface of the metal nanowire array, introducing gallium into contact with the indium layer and causing an alloying reaction.
[0045] In the present application, the specific process of S5 is as follows: take the sample obtained in S4, connect a wire to the edge of the sample through silver paint or conductive glue to ensure electrical conduction; then electrodeposit an indium layer on the surface of the metal nanowire array as an alloying acceptor, control the deposition amount of indium to be 0.3-1.0 mg / cm 2 ; then introduce gallium into contact with the indium layer, form an indium-gallium eutectic alloy through a diffusion reaction, and thus achieve uniform coverage of the liquid metal on the surface of the nanowire array.
[0046] The preparation process of the core layer in the present application is shown in the schematic diagram as Figure 1 shown.
[0047] The structure diagram during the preparation of the core layer in the present application is shown in the schematic diagram as Figure 2 shown.
[0048] In the present application, in S6, the first encapsulation layer and the second encapsulation layer respectively comprise a polyimide film, a polyethylene terephthalate film or a polydimethylsiloxane film.
[0049] In the present application, in S6, before the core layer is laminated and attached for encapsulation, water washing is performed to remove impurities on the surface.
[0050] The present application also provides a flexible self-healing electrode with a micro-bump-nanowire array structure, which is prepared according to the preparation method of the flexible self-healing electrode with a micro-bump-nanowire array structure.
[0051] The present application also provides an application of the flexible self-healing electrode with a micro-bump-nanowire array structure in a flexible electronic device.
[0052] The present application is further described below in conjunction with the accompanying drawings and examples. Unless otherwise defined, the technical terms or scientific terms used in the present application shall have the usual meanings understood by those skilled in the art. The features mentioned in the present application or the features mentioned in the specific examples can be combined in any manner, and these specific examples are only used to illustrate the present application and are not used to limit the scope of the present application.
[0053] Example 1 The present embodiment provides a preparation method of a flexible self-healing electrode with a micro-bump-nanowire array structure, which comprises the following steps: Dimethyl methyl hydrogen (silicone and polysiloxane) and methyl vinyl cyclosiloxane are mixed in a mass ratio of 10:1, stirred for 7.5 min to obtain a slurry; vacuum extraction is performed to 0.1 MPa, the defoaming treated slurry is coated on a 1000 mesh sandpaper, and placed on a flat spin coater stage, and spin coating is performed at a speed of 200 rpm to make the slurry uniform in thickness at each place of the template, then placed at room temperature for 30 min, and then cured in a vacuum drying box at a temperature of 80℃ for 2 h, peeled off to obtain a flexible substrate with a microstructure (labeled as PDMS) with a thickness of 600 μm.
[0054] The flexible substrate with a microstructure is immersed in ethanol and ultrasonically treated at 180 W for 15 min, taken out after the end, immersed in a 65% nitric acid solution, and kept in a 30℃ constant temperature water bath for 20 min, then the sample is washed with a large amount of water and dried with N2; under N2 atmosphere, the temperature is raised to 150℃ at a rate of 3.5℃ / min, and kept at this temperature for 1.5 h, so as to form a micro-bump structure on the surface of the flexible substrate. Then oxygen plasma treatment is performed, the discharge power is set to 200 W, the oxygen flow is set to 20 sccm, and the time is set to 150 s.
[0055] A 5% by mass polyvinyl alcohol solution was prepared by slowly adding polyvinyl alcohol to 20 mL of water in multiple portions, allowing the solution to stand for 10 min, and then heating and stirring the solution at 90°C for 60 min and at 65°C for 180 min. After cooling to room temperature, the solution was made up to its original mass by adding water to compensate for evaporation. The flexible substrate treated by oxygen plasma was immersed in the 5% by mass polyvinyl alcohol solution for 10 min. After the immersion, the sample was removed, held with tweezers, and gently wiped to remove residual droplets. The sample was then placed on a hot plate heated uniformly at 90°C to dry the sample.
[0056] The flexible substrate treated as described above was placed in a sputtering chamber, argon gas was introduced into the chamber, and a titanium layer was sputtered for 300 s at a sputtering power of 150 W and a sputtering temperature of 120°C. The deposition rate was controlled at 20 nm / min by adjusting the gas pressure. A copper layer was then sputtered for 90 min to form a copper seed layer.
[0057] PdCl2(5 mg) was slowly added to 20 mL of a 0.1 mol / L hydrochloric acid solution, which was stirred at 50°C until the PdCl2was completely dissolved. Water was added to obtain 50 mL of an activation solution containing metal ions. The flexible substrate on which the copper seed layer was deposited was immersed in the activation solution containing metal ions and activated at 40°C for 5 min. After the activation, the sample was removed and washed with water. The sample was then dried under a nitrogen atmosphere for 1.5 min.
[0058] In a fume hood, 100 mL of water was used to dissolve 30 mg of sodium citrate, followed by the addition of 25 mg of copper sulfate pentahydrate. After stirring until complete dissolution, the pH of the system was adjusted to 9 using a 0.3 mol / L sodium hydroxide solution to obtain a mixed solution. The sample was fixed horizontally with the upper surface facing upwards and immersed in the mixed solution at a temperature of 60°C. The edge of the sample was kept 12 mm from the liquid surface. After placing the sample, 150 mL of a 0.3 mol / L ascorbic acid solution was slowly added dropwise. Gentle stirring was maintained throughout the reaction. After 30 min, the sample was removed and quickly immersed in water for 1 min. The sample was then dried under a stream of N2to obtain a sample piece. A metal nanowire array was formed on the surface of the flexible substrate in the sample piece (labeled Cu / PDMS).
[0059] The obtained sample is connected with a conductive wire at its edge through conductive glue, and then an indium layer is electrodeposited on the surface of the metal nanowire array to construct an alloying acceptor. The preparation process of the electrodeposition solution comprises the following steps: dissolving InCl3·4H2O and NH4Cl in an indium chloride solution with a mass fraction of 2.2%, and then adding a hydrochloric acid solution with a mass fraction of 37% to adjust the pH to 4.5 to obtain the electrodeposition solution, wherein the concentration of InCl3·4H2O in the electrodeposition solution is 20 g / L, and the concentration of NH4Cl is 50 g / L. The specific process of electrodeposition comprises the following steps: washing the sample with water, connecting the sample to the negative electrode, connecting the Pt electrode to the positive electrode, and then placing them together in the electrodeposition solution, and depositing for 10 min under the conditions of a current density of 5 mA / cm 2 , a temperature of 30℃, and a deposition voltage of 2.5V, and then washing with water after the deposition is completed, and the obtained sample is marked as In / Cu / PDMS, and the deposition amount of indium is 0.65 mg / cm 2 .
[0060] Then, gallium is introduced and alloyed, 1 mL of liquid gallium is added on the surface of the indium layer, the sample is placed in a hydrochloric acid atmosphere to thin the oxide skin of gallium, 1 mL of a hydrochloric acid solution with a mass fraction of 37% is then added on the surface to completely destroy the oxide layer, so that the internal liquid gallium fully wets the surface of the sample, and then a scraper is used to scrape it flat to achieve uniform coverage and remove the excess part. After the diffusion reaction, indium and gallium form a eutectic alloy, realizing uniform coverage of the liquid metal on the surface of the nanowire array, and finally a core layer (marked as Ga / Cu / PDMS) is obtained.
[0061] Finally, the core layer is washed with water, and the core layer is laminated and packaged in the order of polyimide film, core layer, and polyimide film to obtain a flexible self-healing electrode with a micro-bump-nanowire array structure.
[0062] Embodiment 2 The embodiment provides a preparation method of a flexible self-healing electrode with a micro-bump-nanowire array structure, which is different from embodiment 1 in that the discharge power of the oxygen plasma treatment is modified to 100 W.
[0063] Embodiment 3 The embodiment provides a preparation method of a flexible self-healing electrode with a micro-bump-nanowire array structure, which is different from embodiment 1 in that the oxygen flow rate of the oxygen plasma treatment is modified to 40 sccm.
[0064] Embodiments 4-7 Embodiments 4-7 respectively provide a preparation method of a flexible self-healing electrode with a micro-bump-nanowire array structure, which is different from embodiment 1 in that the mass fraction of the polyvinyl alcohol solution is modified to 4% (embodiment 4), 3% (embodiment 5), 2% (embodiment 6), and 1% (embodiment 7).
[0065] Examples 8-11 Examples 8-11 respectively provide a preparation method of a flexible self-healing electrode with a micro-peak-nanowire array structure, which is different from Example 2 in that the mass fraction of the polyvinyl alcohol solution is modified to 4% (Example 8), 3% (Example 9), 2% (Example 10), and 1% (Example 11).
[0066] Examples 12-14 Examples 12-14 respectively provide a preparation method of a flexible self-healing electrode with a micro-peak-nanowire array structure, which is different from Example 1 in that the mesh number of the sandpaper is modified to 600 mesh (Example 12), 400 mesh (Example 13), and 220 mesh (Example 14).
[0067] Examples 15-17 Examples 15-17 respectively provide a preparation method of a flexible self-healing electrode with a micro-peak-nanowire array structure, which is different from Example 4 in that the mesh number of the sandpaper is modified to 600 mesh (Example 15), 400 mesh (Example 16), and 220 mesh (Example 17).
[0068] Examples 18-20 Examples 18-20 respectively provide a preparation method of a flexible self-healing electrode with a micro-peak-nanowire array structure, which is different from Example 5 in that the mesh number of the sandpaper is modified to 600 mesh (Example 18), 400 mesh (Example 19), and 220 mesh (Example 20).
[0069] Examples 21-23 Examples 21-23 respectively provide a preparation method of a flexible self-healing electrode with a micro-peak-nanowire array structure, which is different from Example 6 in that the mesh number of the sandpaper is modified to 600 mesh (Example 21), 400 mesh (Example 22), and 220 mesh (Example 23).
[0070] Examples 24-26 Examples 24-26 respectively provide a preparation method of a flexible self-healing electrode with a micro-peak-nanowire array structure, which is different from Example 7 in that the mesh number of the sandpaper is modified to 600 mesh (Example 24), 400 mesh (Example 25), and 220 mesh (Example 26).
[0071] Comparative Example 1 Comparative Example 1 provides a preparation method of a flexible self-healing electrode with a micro-peak-nanowire array structure, which is different from Example 1 in that the mesh number of the sandpaper is modified to 0.
[0072] Comparative Example 2 Comparative Example 2 provides a preparation method of a flexible self-healing electrode with a micro-bump-nanowire array structure, which is different from Example 4 in that the grit number of the sandpaper is modified to 0.
[0073] Comparative Example 3 Comparative Example 3 provides a preparation method of a flexible self-healing electrode with a micro-bump-nanowire array structure, which is different from Example 5 in that the grit number of the sandpaper is modified to 0.
[0074] Comparative Example 4 Comparative Example 4 provides a preparation method of a flexible self-healing electrode with a micro-bump-nanowire array structure, which is different from Example 6 in that the grit number of the sandpaper is modified to 0.
[0075] Comparative Example 5 Comparative Example 5 provides a preparation method of a flexible self-healing electrode with a micro-bump-nanowire array structure, which is different from Example 7 in that the grit number of the sandpaper is modified to 0.
[0076] Experimental Example 1 The flexible substrate with microstructure (labeled as PDMS) with a thickness of 600 μm in Example 1, the flexible substrate (labeled as PDMS-A) treated by a polyvinyl alcohol solution in Examples 1-26 and Comparative Examples 1-5 were respectively subjected to contact angle test according to GB / T 30693-2014, and the contact angle diagrams of different flexible substrates in Examples 1-3 were obtained, as shown in FIGS. 1-3. Figure 3 Figure 3 a) in FIG. 1 is the contact angle diagram of PDMS in Example 1, Figure 3 b) in FIG. 2 is the contact angle diagram of PDMS-A in Example 3, Figure 3 c) in FIG. 3 is the contact angle diagram of PDMS-A in Example 2, Figure 3 d) in FIG. 4 is the contact angle diagram of PDMS-A in Example 1. The contact angle diagrams of PDMS-A in Examples 1, 2 and 4-11 are shown in FIG. 5, and the contact angle diagrams of PDMS-A in Examples 1, 4-7, 12-26, Comparative Examples 1-5 are shown in FIG. 6. Among them, the smaller the contact angle, the better the adhesion of the polydimethylsiloxane surface. It can be obtained from FIGS. 5 and 6 that the polydimethylsiloxane surfaces in the examples all have good adhesion, and the adhesion of the polydimethylsiloxane surface in Example 1 is the best. Figure 4 Figure 5 Figures 3-5
[0077] Experimental Example 2 The PDMS, Cu / PDMS and Ga / Cu / PDMS in Example 1 are respectively subjected to physical characterization, and the physical characterization graphs of the PDMS, Cu / PDMS and Ga / Cu / PDMS in Example 1 are obtained, as shown in Figure 6 , Figure 6 a) in the figure is the physical characterization graph of the PDMS in Example 1, Figure 6 b) in the figure is the physical characterization graph of the Cu / PDMS in Example 1, Figure 6 c) in the figure is the physical characterization graph of the Ga / Cu / PDMS in Example 1. In addition, the flow schematic diagram of obtaining In / Cu / PDMS from Cu / PDMS in Example 1 is as shown in Figure 7 .
[0078] Experimental Example 3 Scratches are respectively made on the Cu / PDMS and Ga / Cu / PDMS in Example 1, and then the surface morphology at the crack is observed by a microscope, and the morphology characterization comparison graph after the scratches are made by different materials in Example 1 is obtained, as shown in Figure 8 ; Figure 8 a) in the figure is the morphology characterization graph after the scratches are made by the Cu / PDMS, Figure 8 b) in the figure is the morphology characterization graph after the scratches are made by the Ga / Cu / PDMS. From Figure 8 , it can be obtained that when the fatigue cracks are generated on the electrode surface, the porous network composed of Cu nanowires can provide effective capillary driving paths for the flow of Ga. At the moment of crack formation, the liquid metal can rapidly penetrate into the crack area along the nanowire gap, and realize the rapid reconstruction of the conductive loop. The micro-convex peak structure plays a role in dispersing stress on the macro level, and the nanowires simultaneously provide conductive channels and liquid metal transport paths on the micro level; under the synergistic action of the two, not only the capillary and wetting effect is used to promote the rapid flow of Ga into the crack, but also the liquid storage capacity and strong interface bonding of the micro-convex peak are used to make the liquid metal stably stay at the damage position, so that the healing efficiency and reliability of the electrode are significantly improved.
[0079] Therefore, the preparation method of the flexible self-healing electrode with the micro-convex peak-nanowire array structure is adopted, the excellent room temperature fluidity and high conductivity of the liquid metal are used, and the capillary action and liquid storage space provided by the micro-convex peak-nanowire array structure are combined, when the electrode generates cracks due to fatigue, the liquid metal can rapidly flow to and fill the damage area, and automatically restore the conductive path, so that the efficient self-healing without external intervention is realized, and the reliability of the device in a long-term and dynamic working environment is significantly improved.
[0080] It should be pointed out finally that the above examples are only used to illustrate the technical solutions of the present application but not to limit it, and although the present application has been described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present application can still be modified or replaced equivalently, and these modifications or equivalent replacements should not make the modified technical solutions deviate from the spirit and scope of the technical solutions of the present application.
Claims
1. A method for preparing a flexible self-healing electrode with a microbump-nanowire array structure, characterized in that, The method comprises the following steps: S1. providing a flexible substrate with a microstructure; S2. sequentially performing acid etching treatment and heat treatment on the flexible substrate in S1 to form a micro-convex peak structure on the surface of the flexible substrate; S3. sequentially performing oxygen plasma treatment and polymer solution treatment on the flexible substrate treated in S2; S4. forming a metal nanowire array on the surface of the flexible substrate treated in S3; S5. forming a liquid metal layer on the surface of the metal nanowire array to obtain a core layer; S6. laminating and bonding the layers in the order of a first encapsulation layer, the core layer, and a second encapsulation layer to obtain a flexible self-healing electrode with a micro-convex peak-nanowire array structure.
2. The method of claim 1, wherein the flexible self-healing electrode having a micro-peak-nanowire array structure is prepared by the steps of: In S1, the provision of the flexible substrate with a microstructure comprises: mixing a polydimethylsiloxane prepolymer and a curing agent, coating on a template, and peeling off after curing to obtain a flexible substrate with a microstructure.
3. The method of claim 2, wherein the method further comprises: The mass ratio of the polydimethylsiloxane prepolymer to the curing agent is (8-12):1; the template comprises sandpaper; the curing temperature is 75-85℃, and the curing time is 1.5-2.5h.
4. The method for preparing a flexible self-healing electrode with a micro-peak-nanowire array structure according to claim 1, characterized in that, In S2, the acid etching treatment comprises: immersing the flexible substrate in a nitric acid solution; the immersion temperature is 25-40℃, and the immersion time is 10-30min. In S2, the heat treatment is performed in an inert atmosphere; the heat treatment has a heating rate of 2-5℃ / min, a target temperature of 145-155℃, and a holding time of 1-2h.
5. The method for preparing a flexible self-healing electrode with a micro-peak-nanowire array structure according to claim 1, characterized in that, In S3, the oxygen plasma treatment has a discharge power of 100-200W and an oxygen flow rate of 20-40sccm. In S3, the polymer solution treatment comprises: immersing the flexible substrate treated by the oxygen plasma treatment in a polyvinyl alcohol solution with a mass fraction of 1-5% for 5-15min.
6. The method of claim 1, wherein the flexible self-healing electrode having a micro- bump-nanowire array structure is prepared by the steps of: In S4, the formation of the metal nanowire array on the surface of the flexible substrate treated in S3 comprises: (1) depositing a metal seed layer on the surface of the flexible substrate by a magnetron sputtering method; (2) immersing the flexible substrate with the deposited metal seed layer in an activation solution containing metal ions for activation treatment; (3) immersing the flexible substrate after the activation treatment in an aqueous solution containing a metal salt and a reducing agent for reaction to grow a metal nanowire array on the surface of the flexible substrate.
7. The method for preparing a flexible self-healing electrode with a micro-peak-nanowire array structure according to claim 1, characterized in that, In S5, the formation of the liquid metal layer on the surface of the metal nanowire array comprises: electrodepositing an indium layer on the surface of the metal nanowire array, introducing gallium to contact the indium layer and causing an alloying reaction.
8. The method for preparing a flexible self-healing electrode with a micro-peak-nanowire array structure according to claim 1, characterized in that, In S6, the first encapsulation layer and the second encapsulation layer each comprise a polyimide film, a polyethylene terephthalate film, or a polydimethylsiloxane film.
9. A flexible self-healing electrode having a microbump-nanowire array structure, characterized in that, The flexible self-healing electrode with a micro-convex peak-nanowire array structure is prepared by the method according to any one of claims 1-8.
10. The flexible self-healing electrode with a micro-convex peak-nanowire array structure according to claim 9 is applied in a flexible electronic device.